Pengaruh Inisiasi Menyusu Dini (IMD) terhadap Jumlah Perdarahan Kala IV Persalinan di Desa Bangunrejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2024 - Ika Damayanti Sipayung (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
One of the MGDS global targets is to reduce MMR and IMR. The maternal mortality rate in Indonesia is still high at 390 per 100,000 live births. Referring to the link between birth management and various countermeasures for the biggest cause of AKI is postpartum hemorrhage. Efforts have been made in problems related to bleeding, even several studies have carried out IMD in treating bleeding problems considering that the presence of IMD can affect the hormone oxytocin which is associated with bleeding. The purpose of this study was to see how IMD influences the amount of bleeding in the fourth stage.This research is a Quasi Experiment using primary data. The population and sample were all primiparous women with a total of 46 respondents using the purposive sampling method. The data analysis was univariate and bivariate using the Independent t-test. The results showed that there was a significant effect between IMD on the amount of bleeding in the fourth stage. The average number of bleeding in the fourth stage of respondents who underwent Early Breastfeeding Initiation was 150.63 with a standard deviation of 22.149. Meanwhile, for respondents who did not undergo Early Breastfeeding Initiation, the average number of bleeding in the fourth stage was 166.09 with a standard deviation of 21.580. In the statistical test, the value of P = 0.000 was obtained. With this study, it was found that there was an effect of IMD on the amount of bleeding in the fourth stage of labor. It is hoped that midwives and doctors will implement IMD in order to reduce morbidity and mortality of mothers and babies.